2007
DOI: 10.1111/j.1365-2443.2007.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin sensitivity of the Schizosaccharomyces pombe tor2 mutant and organization of two highly phosphorylated TOR complexes by specific and common subunits

Abstract: Nutrients are essential for cell growth and division. Screening of Schizosaccharomyces pombe temperature-sensitive strains led to the isolation of a nutrient-insensitive mutant, tor2-287 . This mutant produces a nitrogen starvation-induced arrest phenotype in rich media, fails to recover from the arrest, and is hypersensitive to rapamycin. The L2048S substitution mutation in the catalytic domain in close proximity to the adenine base of ATP is unique as it is the sole known genetic cause of rapamycin hypersens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
280
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(291 citation statements)
references
References 53 publications
11
280
0
Order By: Relevance
“…Later, it was found that Tor1 is the catalytic subunit of TORC2 while Tor2 is the catalytic subunit of TORC1. TORC1 also contains the protein Mip1 (raptor in humans), and TORC2 also contains the proteins Ste20 (rictor in humans) and Sin1 (mSin1 in humans) (13)(14)(15)(16)(17)(18)(19)(20). TORC1 is essential under normal growth conditions and plays major roles in the control of cellular growth, possibly in response to nitrogen availability (17,(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Later, it was found that Tor1 is the catalytic subunit of TORC2 while Tor2 is the catalytic subunit of TORC1. TORC1 also contains the protein Mip1 (raptor in humans), and TORC2 also contains the proteins Ste20 (rictor in humans) and Sin1 (mSin1 in humans) (13)(14)(15)(16)(17)(18)(19)(20). TORC1 is essential under normal growth conditions and plays major roles in the control of cellular growth, possibly in response to nitrogen availability (17,(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Genome instability also occurs in clk-2 mutant germlines, but strong alleles lead to a late G2-like cell cycle arrest. Subsequent studies on mammalian and yeast CLK-2 orthologs, referred to as TEL2 in yeasts, established that CLK-2/TEL2 is required for the full activation of all PIKKs-type protein kinases, a class of protein kinases that includes ATM/ atm-1 and ATL-1, thus explaining checkpoint-signalling phenotypes (Hayashi et al 2007 ;Kanoh and Yanagida 2007 ;Hurov et al 2010 ;Takai et al 2010 ;Kaizuka et al 2010 ) . The current model suggests that CLK-2/TEL2 might have a chaperonlike function required for the full activation of those kinases (Horejsi et al 2010 ) .…”
Section: Upstream Dna Damage Checkpoint Signalling In the C Elegans mentioning
confidence: 99%
“…These were numbered based on their order of discovery. Later, it was found that Tor1 interacts with Ste20 (Rictor) and Sin1 to form TORC2, whereas Tor2 interacts with Mip1 (Raptor) to form TORC1 (10,11). As in human cells, S. pombe TORC1 is negatively regulated by the TSC complex (12,13).…”
mentioning
confidence: 99%